Influencing Factors of Customers Brand Advocacy Starbucks - Fortunatus, Angela Eunike; Berlianto, Margaretha Pink (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to determine the influence of Brand Experience (Sensory, Affective, Behavioral, and Intellectual) on Customer Satisfaction. Brand Trust and Brand Loyalty on Brand Advocacy. Customer Satisfaction, Brand Trust and Brand Loyalty as Mediating Variable. Descriptive research design used with a quantitative research method and non-probability sampling technique used with purposive sampling resulting in a sample size of 217 respondents. Questionnaire used to collect the data which then processed using the SmartPLS program version 4. The results indicates there’s no positive effectof SBE on Customer Satisfaction. There’s a positive efffect of ABE, BBE, and IBE on Customer Satisfaction. There’s a positive efffect of Customer Satisfaction on Brand Trust and Brand Loyalty. There’s a positive efffect of Brand Trust on Brand Loyalty. There’s a positive efffect of Brand Trust and Brand Loyalty on Brand Advocacy. his study has several implications for management, including coffee shop industry managers need to improve Affective, Behavioral, and Intellectual Brand Experience to elevate customer satisfaction, trust, and loyalty therefore brand advocacy will increase.